Early newborn bathing practice and its determinants among postpartum women in Ethiopia: a systematic review and meta-analysis - Addis Eyeberu; Tamirat Getachew; Ayenachew Kebad; Adera Debella (BMC Pregnancy and Childbirth, 2024)
Abstract Background Early baby bathing has a major negative impact on the newborn's health. Even though early newborn bathing has numerous detrimental effects on neonatal health, evidence has provided little attention on the current level of practice. Furthermore, there is a dearth of data regarding the overall effects of early newborn bathing in Ethiopia, which would be helpful to program and policy designers. This meta-analysis aimed to ascertain the level of early bathing practice and its determinants among postpartum women in Ethiopia. Methods All articles were searched from the Web of Sciences, CINAHL (EBOSCO), Science Direct, MEDLINE, PubMed, Google Scholar, and Google websites from inception to October 10, 2023. The meta-analysis was performed using Stata version 18. The summary estimates with 95% CI were estimated using the random effect model with the Der Simonian Liard method. Heterogeneity was explored using Galbraith plot, Cochrane Q statistics, I2 statistics, and test of theta. To deal with the observed heterogeneity, subgroup analysis, sensitivity analysis, and meta-regression were done. Results This meta-analysis included a total of 2787 postpartum women. The pooled level of early newborn bathing practice among postpartum women in Ethiopia was 55% [95% CI: 38–71]. Based on subgroup analysis by region, the highest level of early newborn bathing practice was among studies conducted in the Afar region which was 73% (95% CI: 69–77). There is a significant association between maternal level of education and early newborn bathing practice among postpartum women in Ethiopia (AOR = 0.51, 95% CI: 0.24, 0.78). Conclusions In this meta-analysis, the overall estimate illustrates that more than half of postpartum women practice early newborn bathing in Ethiopia. Maternal level of education was significantly associated with early newborn bathing practice. Thus, both the government and all the concerned stakeholders should take coordinated action to boost information dissemination and awareness creation among postpartum women thereby reducing the practice of early newborn bathing and alleviating consequences of early newborn bathing.